A Bivalent Human Adenovirus Type 5 Vaccine Expressing the Rabies Virus Glycoprotein and Canine Distemper Virus Hemagglutinin Protein Confers Protective Immunity in Mice and Foxes - Yan, Lina; Zhao, Zhongxin; Xue, Xianghong; Zheng, Wenwen; Xu, Tong; Liu, Lele; Tian, Li; Wang, Xianwei; He, Hongbin; Zheng, Xuexing (Frontiers in Microbiology, 2020)
Rabies virus (RABV) and canine distemper virus (CDV) both are contagious antigens in global canine populations and cause server even lethal diseases in many mammals. In this study, a replication-deficient human adenovirus 5 (Ad5)-vectored vaccine stain, rAd5-G-H, co-expressing RABV glycoprotein (G) and CDV hemagglutinin (H) were constructed. The expression of RABV G and CDV H in Vero cells infected with rAd5-G-H was confirmed by indirect immunofluorescence assay (IFA). The rAd5-G-H demonstrated homogeneous icosahedral morphology similar to rAd5-GFP in electron microscope. A single dose of rAd5-G-H 108 GFU in mice or 109 GFU in foxes elicited rapid and robust neutralizing antibody responses against both RABV and CDV by intramuscular injection. Compared to the mock and rAd5-GFP inoculation group, dendritic cells and B cells were significantly recruited in inguinal lymph nodes in mice immunized rAd5-G-H by flow cytometry assays. Also, rAd5-G-H elicited both the Th1 and Th2 mediated cell immune responses to RABV and CDV in immunized mice, and all the mice survived of a lethal dose challenge of RABV with no clinical signs. In foxes, a single dose of rAd5-G-H 109 GFU also induced significant neutralizing antibody response against RABV and CDV in comparison of rAd5-GFP and mock groups. All foxes in rAd5-GFP and mock groups died, but all the foxes inoculated with rAd5-G-H were survived with no symptoms of disease after a lethal challenge of wild type CDV. These results suggested that rAd5-G-H served as a bivalent vaccine candidate with great potential against rabies and canine distemper in fur animals.